Donation after circulatory death and liver transplantation: a cohort study. (8th June 2021) - Passamonti, Serena Maria; Cannavò, Antonino; Panigada, Mauro; Trunzo, Valentina; Bottazzi, Andrea; Longobardi, Antonio; Buonocore, Ruggero; Fiorattini, Andrea; Torelli, Rosanna; Piccolo, Giuseppe; De Feo, Tullia Maria
Summary: Donations after circulatory death (DCD) are still challenging in Italy because of prolonged ischemia time (tWIT) due to the law and logistical issues. This cohort study was primarily aimed at assessing the association between successful transplantation and DCD types in the North Italy Transplant program. Adjusted risk ratios (RR) and 95% confidence intervals (CIs) for type III versus type II DCD were estimated using a Poisson regression model with a robust error variance. All consecutive DCD between 2008 and 2020 were included. Among 142 DCD, 102 were eligible for liver donation, and 96 were proposed: 68/69 (99%) and 28/33 (85%) type III and II DCD, respectively. Sixty‐nine livers were recovered, 51/68 (75%) from type III and 18/28 (64%) from type II DCD, respectively (RR: 1.18; 95% CI: 0.87–1.60). After ex‐vivo perfusion, 50/68 (74%) and 14/28 (50%) livers from type III and type II DCD were transplanted (RR: 1.49; 95% CI: 1.01–2.19). The estimate decreased after further controlling for tWIT (RR: 1.11; 95% CI: 0.55–2.24). Five patients (7.8%) experienced a PNF, 3/50 and 2/14 from type III and type II DCD, respectively. Type III DCD livers were more likely to be transplanted than type II. Warm ischemia time might explain this difference.